The Effect of Profitability, Leverage and Institutional Ownership on Corporate Social Responsibility Disclosure - Ni Luh Putu Rastika Dewi; Ni Made Adi Erawati (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the effect of profitability, leverage and institutional ownership on Corporate Social Responsibility Disclosure in health sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. This study uses secondary data in the form of annual reports and sustainability reports from 20 health sector companies during the 2021-2023 period, with a total of 60 observations selected using purposive sampling technique. Data analysis was carried out using multiple linear regression methods using the SPSS program. The results showed that profitability and leverage have no effect on CSR disclosure. Institutional ownership has a positive effect on CSR disclosure of health sector companies in Indonesia.